ED014. The undervalued fauna of subterranean ecosystems. Case study: Puyu Yaku cave circuit in Mera canton, Pastaza province – Ecuador - Díaz Guevara, David R. (2023)
Underground ecosystems are sites of geological, ecological, economic, and cultural interest. However, in Ecuador, they are few studied ecosystems at a biological level, so the underground fauna has remained unknown over the years. These organisms often have peculiar adaptations due to the hostile ecosystem where they develop, where there is no solar incidence and therefore the flow of matter and energy is different from the rest of known ecosystems. That is why this research pretends to demonstrate the high possibility to find new discoveries for science, the high diversity of invertebrates that these ecosystems may have and thus enhance the bio speleological research in Ecuador. To do this, different subterranean organisms, terrestrial and aquatic, were studied. They were collected through the interaction of three different methods, such as: manual collection, pitfall traps and finally the implementation of a “D” type network in Puyo – Yaku caves, where 45 morphospecies were found, some of them with troglomorphisms and at least two possible new discoveries for science, however it is suggested to plan new sampling methodologists considering different times of the year.